CORPORATE GOVERNANCE, FINANCING RISK, SHARIAH COMPLIANCE DAN EARNING MANGEMENT TERHADAP KINERJA KEUANGAN BANK UMUM SYARIAH DI INDONESIA - Hidayah, Syarifatul; Yasin, Ach (Jurnal Ekonomika dan Bisnis Islam, 2023)
Islamic Commercial Banks are expected to carry out corporate, risk, compliance to improve the financial performance of Islamic Commercial banks in Indonesia. This study aims to determine whether there is an influence of corporate governance, financing risk, shariah compliance, and earning management on financial performance.  The research method used in the study is a quantitative approach with secondary data. Data was taken with purposive sampling technique. The results of this study indicate that corporate governance as measured by DPS and KA has no influence on financial performance. NPF affects the financial performance of Islamic Commercial Banks, FDR has no influence on financial performance. For shariah compliance, measurement using PSR shows influential results and IsIR has no influence on the financial performance of Islamic Commercial Banks in Indonesia. Meanwhile, earning management has no influence on the financial performance of Islamic Commercial Banks. So, with the results obtained from this research, Islamic Commercial Banks can pay more attention to the financing portolio, especially mudharabah and musyarakah financing, so that they can run more effectively and reduce losses in order to improve the bank’s overall financial performance.